Differences in the validity of a visual estimation method for determining patients' meal intake between various meal types and supplied food items. Issue 1 (February 2019) - Kawasaki, Yui; Akamatsu, Rie; Tamaura, Yuki; Sakai, Masashi; Fujiwara, Keiko; Tsutsuura, Satomi
Summary: Background & aims: The aim of this study was to examine differences in the validity of a visual estimation method for determining patients' meal intake between various meal types and supplied food items in hospitals and to find factors influencing the validity of a visual estimation method. Methods: There are two procedures by which we obtained the information on dietary intake of the patients in these hospitals. These are both by visual assessment from the meal trays at the time of their clearing, by the attending nursing staff and by weighing conducted by researchers. The following criteria are set for the target trays: A) standard or therapeutic meals, which are monitored by a doctor, for energy and/or protein and/or sodium; B) regular, bite-sized, minced and pureed meal texture, and C) half-portion meals. Visual assessment results were tested for their validity by comparing with the corresponding results of weighing. Differences between these two methods indicated the estimated and absolute values of nutrient intake. Results: A total of 255 (76.1%) trays were included in the analysis out of the 335 possible trays and the results indicated that the energy consumption estimates by visual or weighing procedures are not significantly different (412 ± 173 kcal, p = 0.15). However, the mean protein consumption was significantly different (16.3 ± 6.7 g/tray, p < 0.01) between the two procedures. Compared with standard meals (38 ± 45 kcal, 1.9 ± 2.5 g/tray), raters significantly misestimated the energy and protein intake of half-portion meals (78 ± 65 kcal, 2.8 ± 2.2 g/tray, p = 0.01) but accurately estimated the protein intake of protein controlled meals (0.5 ± 0.6 g/tray, p = 0.03). Trays adding supplied food items were significantly misestimated for energy intake (66 ± 58 kcal/tray) compared to trays with no additions (32 ± 39 kcal/tray, p < 0.01). Moreover, the results of multivariable analysis demonstrated that supplied food items were significantly associated with increased odds of a difference between the two methods (OR: 3.84; 95% confidence interval [CI]: 1.07–13.85). Conclusions: There were high correlations between the visual estimation method and the weighing method measuring patients' dietary intake for various meal types and textures, except for meals with added supplied food items. Nursing staff need to be attentive to supplied food items.